Role Playing and the Changing of Teacher Understanding to Middle School Mathematics Lesson Planning within ELPSA Framework - Kinasih, Indira Puteri; Hardiani, Nur (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2020)
The lesson plan plays an important role in the achievement of learning objectives. This paper aimed to describe the effect of lesson plan role play on changes in teacher understanding regarding the process of mathematics lesson plan writing using the ELPSA framework. The method used was descriptive qualitative. 13 West Nusa Tenggara math teachers were involved through filling out questionnaires about the lesson plan writing habits among teachers, the usefulness of role-playing, and the impact on the lesson plan improvement process they designed. Results showed that the lesson plan role play was able to change the teacher's understanding, particularly on the importance of clear and communicative lesson designs as well as the sequential and anticipatory learning scenarios included. This change in teachers' understanding also has an impact on the awareness of teachers to improve their draft lesson plan in terms of integrated learning indicators, sequentialness, and the content quality of learning activities and clarity of teaching notes that allow the lesson plan to be more explicit and applicable. Overall, it can be concluded that more than 95% of the teacher respondents stated that role play had a positive influence in the form of a willingness to re-reflect and reconstruct each lesson plan. In general, they gain knowledge and awareness about how to build a good lesson plans so that they have the potential to create activities and an atmosphere of teaching and learning that are interactive, focused, and pay attention to what students already know.